Ecosistemas digitales de vigilancia e inteligencia global y su impacto en la Seguridad y Defensa Nacional - Castro Gonzalez, Luis (2024)
The objective of this article was to identify the digital ecosystems of global surveillance and intelligence and how these impact national security and defense. The exponential development of technology and the use of cyberspace has allowed many governments to use global surveillance systems through intelligence. artificial and metadata, at least 77 countries are already using public facial recognition systems, safe cities with intelligent police surveillance techniques, intelligence and counterintelligence activities with massive monitoring of communications; This article seeks to determine exactly what is causing the increase in surveillance and to understand the capabilities of these systems. To address the analysis of this problem, a qualitative approach was used through a hermeneutic interpretive method of the study categories using the documentary technique. The article analyzes aspects such as global surveillance and intelligence and national security and defense; The most significant conclusion of this research is that global surveillance and intelligence significantly impact the national security and defense of countries.